Managing acute alcohol withdrawal with Homoeopathy: A prospective, observational, multicentre exploratory study - Debadatta Nayak (Indian Journal of Research in Homoeopathy, 2014)
Background: Alcohol dependence is a common social problem which may be associated with other risk factors and co-morbidities. Abrupt cessation of alcohol intake may provoke an acute alcohol withdrawal phase with varying degrees of signs and symptoms. In conventional medical system, specific pharmacological interventions are used for management of Acute Alcohol Withdrawal (AAW). There exists a need to explore safe and holistic treatment of AAW. The present work reports the results of a prospective, observational, exploratory, multicentre trial (2008-2011) to assess the role of Homoeopathy in AAW. Materials and Methods: Individualised Homoeopathy was given to 112 patients reporting with AAW. The clinical assessment was done for 05 days using Clinical Institute Withdrawal Assessment Scale of Alcohol-Revised (CIWA-Ar). Post-withdrawal phase, quality of life of patients was assessed at end of 01 st , 03 rd and 06 th month using World Health Organisation quality of life (WHOQOL)- BREF. Results and Analysis: There was a significant decrease in CIWA-Ar mean scores and increase in quality of life score (P < 0.001). The most common remedies used were Arsenicum album, Lycopodium clavatum, Belladonna, Nux vomica and Pulsatilla. Conclusion: The results of current observational pilot study suggest the promising use of Homoeopathy in the management of acute alcohol withdrawal. Further studies with large sample size and rigorous design are warranted.